The Impact of Strategic Human Resources Management to Organizational Citizenship Behavior for the Environment in Manufacturing Company - Pratiwi, Pratiwi; Salsabiela, Aini Zahra (Department of Management, Faculty of Economics and Business, Brawijaya University, 2015)
This study aims to examine the Strategic Human Resource Management (SHRM), Internal Environtmental Orientation (IEO), and Organizational Citizenship Behavior Environment (OCBE) in a manufacturing company in Jakarta and its surrounding areas. It is specifically aimed to identify whether there is an influence of SHRM and IEO to OCBE and to investigate whether the IEO moderately influences SHRM to OCBE. The respondents of this study are employees of manufacturing company from different levels and positions from several industries. The selection of respondents is done by convenience sampling and it successfully collects 150 respondents. The results of descriptive analysis show that SHRM, IEO, and OCBE on the company they work is acceptable but it still needs improvement. In addition it is found that there is a significant positive influence of SHRM and IEO variables to OCBE. However, IEO variable does not moderately influence SHRM to OCBE.